Microwave-Assisted Extraction Combined with Ultra-High-Performance Liquid Chromatography and Quadrupole/Q-Exactive High-Resolution Mass Spectrometry for the Determination of Main Flavor Substances in Green Tea. (20th April 2020) - Qi, Chen; Tianyang, Guo; Jian, Yao; Renyi, Liao; Peng, Wu; Qiong, Wu; Shaotong, Jiang; Yiyang, Dong
Abstract: Background: In order to make up for the efficacy of sensory assessment of green tea quality and taste, main flavor substances should be quantitatively characterized based on efficient extraction and frontier determination scheme. Methods: A new, relatively simple sample preparation and detection workflow has been developed for the quantification and confirmation of flavor substances in green tea by microwave-assisted extraction combined with ultra-high-performance LC and quadrupole/Q-Exactive high-resolution MS system. The method identified main flavor substances (i.e., catechins, free amino acids, and caffeine) that were the main components in the formation of tea taste. After crushing pretreatment, tea was extracted and purified simultaneously in a microwave extraction jar by matrix-dispersed solid-phase extraction. The extracting solution was determined by LC coupled to high-resolution Orbitrap mass spectrometry. Results: In this study, extraction solvent and purification materials were selected, extraction temperature and time were optimized, and the amount and proportion of solid-phase extraction packing were optimized. Conclusions: The method enabled detection of multiple catechins, amino acids, and caffeine in tea by LC coupled to high-resolution Orbitrap MS, and a database of tea flavor substances was established. Highlights: The method could be used for screening and confirmation of the main flavor substances in tea as well as assisting the sensory evaluation to grade the quality of tea.